Innovation from Information Systems An Ambidexterity Approach - Dupouet, Olivier; Bouzdine-Chameeva, Tatiana; Lakshman, C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Relying on the extensive study of a multi-national Company, this work proposes a process view of the way firms balance tensions between exploring new knowledge and exploiting old one. First, ideas are generated throughout the organization. These ideas are funneled towards specific project teams that further develop and refine them. Second, projects are assessed by the top management. Agreed projects are then progressively transformed into exploitable products, following a transformative learning process. We then make propositions regarding the role information systems can play in sustaining this process. Regarding the first phase of the cycle, we will focus on systems that help in sustaining idea generation and in balancing explorative and exploitive projects in the technologies portfolio of the firm. Regarding the second phase, we will look at information systems that could be useful in supporting knowledge transfer and knowledge interpretation across a multi-national company.
Introduction -- Literature Review -- Case Study: The Group Legrand -- Theoretical Framework and Propositions -- Mathematical Modeling -- Conclusions.
Keywords: Economics; Information Systems; Management information systems; Economics/Management Science; Business Information Systems; Innovation/Technology Management; Management of Computing and Information Systems